Influence of genotype and soil on specialized metabolites production and bacterial microbiota associated to wild hop (Humulus lupulus L.): an early-stage study - Ducrocq, Florent; Hafidi, Omar; Grosjean, Jérémy; Hehn, Alain; Piutti, Séverine (Frontiers in Plant Science, 2025)
Hop (Humulus lupulus L.) is a dioecious climbing plant that is emblematic for the brewing industry because of its specialized metabolites. Many studies have focused on hop metabolism without considering the microbiota associated with hop tissues, although over the past decade, a paradigm shift has redefined plants as holobionts, with complex associations between the plant host and its associated microbial communities. In this study, we investigated the effects of three wild hop genotypes cultivated in two different agricultural soils under controlled conditions on specialized metabolite production and on bacterial community composition across different hop compartments (rhizosphere soil, roots, and leaves). Phytochemical analysis of leaf contents revealed distinct metabolic profiles across the six ‘genotype×soil’ interactions, driven by variations in the biosynthesis of prenylated chalcones, α- and β-type bitter acids, and their derivatives. PERMANOVA results demonstrated that both ‘genotype’ and ‘soil’ factors significantly influenced leaf metabolite composition, each explaining approximately 28% of the observed variance. However, the strongest effect was observed for the ‘genotype×soil’ interaction, which accounted for 66% of the variance. In parallel, soil type, hop genotype, and their interaction significantly shape hop-associated bacterial communities, with a predominant interaction effect in each compartment (rhizosphere soil, roots and leaves) (R² = 0.74, 0.74 and 0.32, respectively). Furthermore, Spearman microbiome–metabolome correlation analysis revealed that bacterial families were positively correlated with the biosynthesis of key metabolites, particularly bitter acids. Our findings further suggest that the hop-associated microbiota may contribute to metabolic biosynthesis, opening new perspectives for optimizing metabolite biosynthesis through microbiome manipulation.